A 2D semi-analytical electromagnetic model for cylindrical ICP sources with Faraday shield. Issue 1 (1st April 2022) - Chen, P; Yang, J; Zhou, L; Zuo, C; Li, D; Chen, D
Abstract: Faraday shield(FS) is a metallic shield with slits through which electromagnetic energy is coupled into cylindrical ICP sources. Thus, the effect of FS on the RF field and power coupling is important. A 2D semi-analytical electromagnetic model considering both FS and plasma is proposed. The results compared to a 2D numerical model shows that the semi-analytical model is available in electromagnetic field calculations. It is found that both FS and plasma have no influence on the magnetic field outside them. FS strengthens the electric field around the slits and weakens the electric field around the middle of the stripes, and this effect is due to the gradient field generated by the electric charge accumulated on the FS surfaces. From the point of view of the pure 2D electromagnetic field, FS affects the electric field distribution in a small region, and it seems to not affect the total power coupling into plasma.